The Relationships among Theatrical Components, Experiential Value, Relationship Quality and Relationship Marketing Outcomes- A Case of Theme Park in Taiwan - Tsai, Chin-Fa (School of Tourism Development, Maejo University, Thailand and Asian Tourism Management Association, 2014)
Both marketing practitioners and academic researchers have traditionally recognized the major influence that relationship quality has on relationship marketing outcomes. Differing from the previous studies, this study proposes a more integrated model by including theatrical components and experiential value into the "relationship quality-relationship marketing outcomes” paradigm. The structural relationships among the variables are examined by adopting a structural equation modeling (SEM) approach in a travel-related context. The results confirm the existence of the path "theatrical components -> experiential value->relationship quality-relationship marketing outcomes". ln addition, theatrical components are found to have an indirect rather than a direct effect on relationship marketing outcomes as mediated by experiential value and relationship quality.